PRESEPSI KONSUMEN TERHADAP PENGGUNAAN LOGO HALAL PADA PRODUK UMKM DI KOTA SAMARINDA - Reslianty Rachim; Zulkifli Zulkifli; Abdul Rachim (University of Widya Gama Mahakam Samarinda, 2023)
The aim of this research is to provide an understanding or meaning of the importance of the halal logo on MSME products. The data analysis method used in this research is three types of activities, namely data condensation, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). The results of research using observations, questionnaires and interviews state that it is very important to implement halal certification in Samarinda City. Study to realize certainty of halal products for the Muslim community.